Risiko Paparan Mikroplastik Pada Air Minum Kemasan Bagi Kesehatan Ginjal: Sistematik Literature Review - Nuryanto Nuryanto (Poltekkes Kemenkes Semarang, 2025)
Plastic as drinking water packaging is very massively used today. Globally, the need for plastic for packaging is 31.3%. The use of plastic as drinking water packaging can be a source of microplastic pollution (MPs). Consumption of drinking water contaminated with microplastics can accumulate and risk the decline of the body's organs, including the kidneys. The method of this research is a systematic literature review. Data collection through search of journal articles available on PubMed, Science Direct, Spring, SAGE Journal, ProQuest and Emerald Insight from January 2014 to December 2024. Search results found 2 out of 1200 articles that met the inclusion criteria. Consumption of contaminated bottled water is a risk to the urinary system at the cellular and organ level. Long-term exposure and high doses have the potential to cause kidney health disorders such as kidney stones and kidney failure. Based on this, in the future, it is necessary to develop further research to assess the level of intake of MPs to increase creatinine and urea levels as indicators of impaired kidney function.